Noise annoyance caused by continuous descent approaches compared to regular descent procedures. (October 2017) - White, Kim; Arntzen, Michael; Walker, Francesco; Waiyaki, Fredrick M.; Meeter, Martijn; Bronkhorst, Adelbert W.
Abstract: During Continuous Descent Approaches (CDAs) aircraft glide towards the runway resulting in reduced noise and fuel usage. Here, we investigated whether such landings cause less noise annoyance than a regular stepwise approach. Both landing types were compared in a controlled laboratory setting with a Virtual Community Noise Simulator (VCNS), using four audio samples: an overflight during a regular approach (2000 ft altitude) and three aircraft performing CDAs at respectively 3000, 4000 and 5000 ft. The samples at 2000 ft and 4000 ft were recorded at a countryside road, a 360° photo of which was used for the virtual visuals. The other two CDA samples were derived from the recording at 4000 ft. Participants were asked to rate all flyover samples twice while being immersed in the virtual environment. The CDA at 3000 ft was rated as most annoying, likely due to a longer overflight duration, followed by the regular descent and then the CDAs at 4000 and 5000 ft. As CDAs follow a fairly steady trajectory, it was estimated that they will increase annoyance within an area of approximately 2.5 km 2, as compared to regular landings. Outside of this area, CDAs may instead result in less annoyance than regular landings.